Models of a New World: towards a Synthesis - R. Väyrynen (Контуры глобальных трансформаций: политика, экономика, право, 2019)
Three alternative world orders can be imagined in the post-World War II international relations. During most of the Cold War a bipolar order, centered on the possession of nuclear weapons, existed. This world order was incomplete, however. The United States and the Soviet Union faced each other with equal capacity to destroy each other, but in terms of economic and global influence the United States was superior. The strengthening of economic and technological dynamics increased further the U.S. influence, but also sparked the power of non-states actors, including transnational corporations and banks, independent of states. Simultaneously with the globalization of the world, one could witness the rise of non-state actors in the military and political fields. The emergence of the world order of the third type has sometimes been called the neomedieval world in which some central tenets of feudalism has re-emerged. None of these world order models can be said to dominate in today’s world and none of them is likely to emerge victorious any time soon. In recent times., globalization has suffered from various setbacks and state-centric relations have reemerged. Their focus is not, however, any more on the military competition between the United States and Russia, although some of its elements remain in the arms competition between them. Globalization has brought in new ingredients in the rivalries between states and it has appeared most visibly in the U.S.-Chinese rivalry for economic and technological dominance of the globalized world economy. In other words, a new type of economic bipolarity is winning ground and is only secondarily manifesting itself in military relations. Patterns of warfare has in recent decades been colored by fighting of non-state military forces and the rise of new feudal patterns of behavior, but they have not been pronounced enough to justify the labeling of the entire world order by the name.